การพัฒนาหน้ากากผ้าสะท้อนน้ำทดแทนหน้ากากอนามัยสำหรับบุคลากรทางการแพทย์ - หุตะกมล, ธนิกา; โพชนุกุล, อรพรรณ; พิสิฏฐศักดิ์, เพ็ญวิสาข์ (วารสารศิลปกรรมบูรพา, 2021)
According to the situation of the COVID-19 Corona epidemic worldwide including Thailand, which causing the shortage of surgical masks (Surgical Mask) for medical personnel who are at risk and also face this problem. The basic requirement of surgical mask is to prevent secretions. Therefore, the researchers have developed a new innovation from local materials, using waterproof coatings and mask designs as well as developing suitable forms to use for medical personnel. The ware test showed that the 4th model of the mask was best suited to the manufacture of the medical masks. In order to replace the current shortage of sanitary masks by designing a reflective fabric mask consisting of 3 layers of fabric which the 1st and 2nd layers are reflective fabrics to prevent secretions and the 3rd layer fabric is used mixed polyester cotton to be able to absorb moisture of the secretions that penetrate through it. In the 3rd layer, the researchers designed to fit a filter to protect against PM 2.5 dust and bacteria.